A. MA.RU The Oldest Sumerian Mythological Text about the Flood - Farhad Azeez Hasan; Mawlud Ibrahim Hasan (Zanco Journal of Human Sciences, 2026)
The Sumerian flood myth is one of the most ancient narratives recounting the decline and salvation of humanity. It unfolds through several phases, including creation, punishment, destruction, redemption, regeneration, and immortality. In this myth, Ziusudra is the central figure, and a group of deities—such as An, Enlil, Ninhursag, Nintud, Enki, and Inanna—play prominent and influential roles in the development of the narrative. The structure of the story is built upon five key stages: The pre-flood tranquility, The decree of destruction, Revelation and divine warning, The flood and cosmic silence, Salvation and renewal This study selects the oldest recorded Sumerian version of the flood myth as its core text. Through a mythological-analytical approach, it aims to examine and reconstruct all phases and underlying themes of the text, thereby offering a reinterpretation of the narrative’s foundational structure and internal coherence.